Hubungan varietas dengan pemangkasan daun terhadap pertumbuhan dan produksi tanaman Jagung manis (Zea mays saccaratha Sturt) - Muhammad, Raja; Zulkifli, Zulkifli; lukmanasari, Putri (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2024)
The research was conducted in the experimental garden of the Faculty of Agriculture, Riau Islamic University, Pekanbaru, within 3 months from March to May 2023. This study aims to determine the interaction effect and the main effect of the Relationship between Variety and Leaf Pruning on the Growth and Production of Sweet Corn Plants (Zea mays saccaratha Sturt). This study used a Divided Plots Design (RPT), the main plot was variety and the subplots were pruning. The variety treatment consisted of 4 treatment levels and pruning consisted of 4 treatment levels, so there were 16 treatment combinations with 3 replications. This study consisted of 48 experimental units. Each experimental unit consisted of 4 plants and 2 sample plants, a total of 192 plants. The parameters observed were plant height, age of male flower emergence, weight of cob with cob, length of cob without cob, number of rows in one cob. Observational data were analyzed statistically and conducted with the Honest Real Differences (BNJ) Further Test at the 5% level. The results showed that the interaction relationship between varieties and leaf pruning had a significant effect on all observation parameters. The best treatment was the panglima variety and pruning the lower 1/3 of the leaves. The main plot treatment significantly affected all observation parameters. The best treatment is the panglima variety. The treatment of subplots significantly influenced all observation parameters. The best treatment is leaf pruning 1/3 of the lower leaves.